Hey mhmarefat.
Is this a Bernoulli type DE?
Hi.
first i apologize for my bad english.
I need to solve this equation : ( i have its solution but can't understand some parts of it )
(y^{4} - 3x^{2})dy + xydx = 0 (1)
I use y = t^{a} ــ> dy = at^{a-1}dt (2) and place it in (1) :
a(t^{5a-1} - 3x^{2}t^{a-1})dt + xt^{a}dx = 0
then i don't understand this next part ( I'm typing it from solution of problem ): 5a - 1 = 2 + a - 1 ?
it then calculates a = 1/2 and solves the equation ... i don't get why 5a - 1 = 2 + a - 1 ...
thanks in advance.